MIF/CD74 axis is a target for novel therapies in colon carcinomatosis. Issue 1 (December 2017) - Bozzi, Fabio; Mogavero, Angela; Varinelli, Luca; Belfiore, Antonino; Manenti, Giacomo; Caccia, Claudio; Volpi, Chiara; Beznoussenko, Galina; Milione, Massimo; Leoni, Valerio; Gloghini, Annunziata; Mironov, Alexandre; et al.
Abstract Background Strategies aimed at obtaining a complete cytoreduction are needed to improve long-term survival for patients with colorectal cancer peritoneal carcinomatosis (CRC-pc). Methods We established organoid models from peritoneal metastases of two naïve CRC patients. A standard paraffin inclusion was conducted to compare their 3D structure and immunohistochemical profile with that of the corresponding surgical samples. RNA expression levels of the CRC stem cell marker LGR5 was measured by in situ hybridization. The secretome of organoids was profiled by mass spectrometry. Energy homeostasis of organoids was interfered with 4-IPP and metformin. Biochemical and metabolic changes after drug treatments were investigated by western blot and mass spectrometry. Mitochondria impairment was evaluated by electron microscopy and mitotraker staining. Results The two organoids recapitulated their corresponding clinical samples in terms of 3D structure and immmunoistochemical profile and were positive for the cancer stem cells marker LGR5. Proteomic analyses of organoids highlighted their strong dependence on energy producing pathways, which suggest that their targeting could be an effective therapeutic approach. To test this hypothesis, we treated organoids with two drugs that target metabolism acting on AMP-activated protein kinase (AMPK), the main regulator of cellular energy homeostasis, which may act as metabolic tumour suppressor in CRC. Organoids were treated with 4-IPP, an inhibitor of MIF/CD74 signalling axis which activates AMPK function, or metformin that inhibits mitochondrial respiratory chain complex I. As a new finding we observed that treatment with 4-IPP downregulated AMPK signalling activity, reduced AKT phosphorylation and activated a JNK-mediated stress-signalling response, thus generating mitochondrial impairment and cell death. Metformin treatment enhanced AMPK activation, decreasing the activity of the anabolic factors ribosomal protein S6 and p4EBP-1 and inducing mitochondrial depolarization. Conclusion We provide evidence that the modulation of AMPK activity may be a strategy for targeting metabolism of CRC-pc organoids.